PENENTUAN LIKU KALIBRASI DEBIT (RATING CURVE) PADA MUSIM HUJAN DI DAERAH ALIRAN SUNGAI (DAS) DELI - Andi Setiawan; Edi Susanto (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2019)
Discharge rating curve is a curve that shows the relationship between water level and river flow so that it can be used to predict the amount of discharge in the river. The purpose of this research was to find the equation of the discharge rating curve in the Deli watershed. This research was carried out by analyzing river water discharge and taking water level data using a water level logger with a minimum of twice a week. River water discharge at the study location has a varied value i.e 0,74 – 3,28 m3/sec with an average of 1,06 m3/sec. The determination of the equation of the discharge rating curve uses several methods namely linear, polynomial, power function, logarithmic, and exponential. The results of the study show that the equation with the second order polynomial method has the best level of correlation (r) and RMSE with value r 0.986 and RMSE 0.011. The rating curve equation obtained was Q = 18,97 (h)2 – 1,372(h) + 0.190.